2009
DOI: 10.1088/1748-0221/4/10/p10005
|View full text |Cite
|
Sign up to set email alerts
|

Commissioning of the CMS High Level Trigger

Abstract: The CMS experiment will collect data from the proton-proton collisions delivered by the Large Hadron Collider (LHC) at a centre-of-mass energy up to 14 TeV. The CMS trigger system is designed to cope with unprecedented luminosities and LHC bunch-crossing rates up to 40 MHz. The unique CMS trigger architecture only employs two trigger levels. The Level-1 trigger is implemented using custom electronics, while the High Level Trigger (HLT) is based on software algorithms running on a large cluster of commercial pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…CORAL has recently been and continues to be the most active of the PF sub-projects. To start with, this is the only package used by all three experiments (for conditions data, via COOL by ATLAS [16] and LHCb [17] and directly by CMS [18]; for event tags, via POOL by ATLAS [19]; for geometry and configuration data, directly by ATLAS [20,21] and CMS [22,23]). The support load is high also because of CORAL's role as the gateway to relational databases.…”
Section: Coral -The Common Abstraction Layer For Accessing Relationalmentioning
confidence: 99%
“…CORAL has recently been and continues to be the most active of the PF sub-projects. To start with, this is the only package used by all three experiments (for conditions data, via COOL by ATLAS [16] and LHCb [17] and directly by CMS [18]; for event tags, via POOL by ATLAS [19]; for geometry and configuration data, directly by ATLAS [20,21] and CMS [22,23]). The support load is high also because of CORAL's role as the gateway to relational databases.…”
Section: Coral -The Common Abstraction Layer For Accessing Relationalmentioning
confidence: 99%
“…It operates with negligible deadtime and synchronously with the LHC bunch crossing frequency of 40 MHz. The High Level Trigger (HLT) is implemented across a large cluster of the order of a thousand commercial computers, referred to as the event filter farm [5], and provides further rate reduction to O(100) Hz using filtering software applied to the full granularity data acquired from all detectors. Complete events for the HLT are assembled from the fragments sent from each detector front-end module through a complex of switched networks and "builder units" also residing in the event filter farm.…”
Section: Compact Muon Solenoidmentioning
confidence: 99%
“…5). Studies using full simulation have shown that a precision of ∼ 0.5% can be achieved in the barrel using ∼ 5 fb −1 of data [18].…”
Section: Calorimeter Calibrationmentioning
confidence: 99%